Membangun Dialog Transformatif: Pendekatan Komunikasi Inklusif Untuk Pedagang Asongan Berdasarkan Yohanes 4:1-42 - Harming, Harming; Rujali, Rujali; Lawai, Hendry; Toni, Toni (Kharisma: Jurnal Ilmiah Teologi, 2025)
In an era of increasingly advanced globalization, building intercultural relationships has become a growing challenge. This article examines the application of inclusive communication approaches in the context of street hawkers, a group often marginalized in discussions of social and cultural inclusion. Based on the theological narrative of John 4:1–42, the study identifies key principles of transformative dialogue, such as sensitivity to cultural contexts, expanding the boundaries of diversity, and striving for unity through constructive dialogue. Using a qualitative interpretive method, this research provides an in-depth analysis of the biblical text and its relevance to real social contexts. The findings show that transformative dialogue principles can serve as the foundation for communication strategies that promote social inclusion and intercultural cooperation among street hawkers. This article not only presents a theological analysis but also offers practical insights for developing inclusive and empowering communication strategies in an increasingly diverse society. Di era globalisasi yang semakin maju, membangun relasi antarbudaya menjadi tantangan yang kian kompleks. Artikel ini mengkaji penerapan pendekatan komunikasi inklusif dalam konteks para pedagang kaki lima, kelompok yang sering terpinggirkan dalam wacana inklusi sosial dan budaya. Berdasarkan narasi teologis Yohanes 4:1–42, studi ini mengidentifikasi prinsip-prinsip dialog transformatif seperti kepekaan terhadap konteks budaya, perluasan batas keberagaman, dan upaya mencapai kesatuan melalui dialog konstruktif. Metode yang digunakan adalah kualitatif interpretatif untuk menganalisis teks biblika secara mendalam dan relevansinya dalam konteks sosial konkret. Hasil penelitian menunjukkan bahwa prinsip dialog transformatif dapat menjadi landasan strategi komunikasi guna mendorong inklusi sosial dan kerja sama antarbudaya di kalangan pedagang kaki lima. Artikel ini tidak hanya menawarkan analisis teologis, tetapi juga pandangan praktis untuk mengembangkan strategi komunikasi yang inklusif dan memberdayakan dalam masyarakat yang semakin beragam.